A Statistical Test of the Success of Consolidations - Dewing, A. S. (Quarterly Journal of Economics, 1921)
Nature of the study, 84. — Underlying assumptions of the study, 86. — I. Previous earnings of the representative consolidation compared with actual earnings, 90. — II. Estimated earnings of the representative consolidation compared with actual earnings, 91. — III. First-year earnings of the representative consolidation compared with later earnings, 93. — Table of fundamental data, 95.